Construction, Characterization, Estimation and Performance Analysis of Selection Generalized Nakagami Distributions with Environmental Applications - Mervat Mahdy; Dina Samir (Journal of Statistical Theory and Applications (JSTA), 2020)
In this article, a selection of Nakagami distribution is investigated. Some properties of the model with some plots of the density function are illustrated. Additionally, weighted of the one-sided Gaussian distribution, Generalized Rayleigh distribution are discussed as a special case of Generalized Nakagami distribution. In addition, maximum likelihood estimators are investigated with numerical methods and are compared by four sub-models with a real wave height data set. Finally, a simulation study is presented for parameters.